Neutrino is the Brightest Particle of the Fictitious Micro-world - Smulsky, Joseph J. (European Journal of Applied Sciences, 2023)
During the decay of radioactive radium E, electrons with a continuous spectrum of velocities are emitted. The average energy measured with a calorimeter is 0.36 MeV. Based on the dependence of mass on velocity accepted in the Theory of Relativity, W. Pauli calculated the kinetic energy of the electron and obtained a value of 1.16 MeV. For explaining the excess energy of 0.8 MeV, a new particle, neutrino, was postulated. In the present study, we show that the experimental laws of electromagnetism were misinterpreted in the Theory of Relativity. Using the correct laws, we have derived the right expression for the force exerted on a moving charged particle. This expression depends on the distance from the acting object and on the particle velocity. According to the new expression for the interaction force, the particle mass suffers no change. Therefore, there is no reason to introduce a neutrino. As a result of the electromagnetic interaction, particles move along other trajectories that were not known previously. Therefore, the wrong interpretation of particle motions has led researchers to the introduction of fictitious particles that now in large quantities inhabit the imaginary microcosm. It is necessary to reconsider the erroneous postulates on the basis of real interaction forces. This revision must be started from Rutherford experiments without invoking the Theory of Relativity and Quantum Mechanics.